Facilitating recall and particularisation of repeated events in adults using a multi-method interviewing format. Issue 4 (21st April 2021) - Kontogianni, Feni; Rubinova, Eva; Hope, Lorraine; Taylor, Paul J.; Vrij, Aldert; Gabbert, Fiona
ABSTRACT: Reports about repeated experiences tend to include more schematic information than information about specific instances. However, investigators in both forensic and intelligence settings typically seek specific over general information. We tested a multi-method interviewing format (MMIF) to facilitate recall and particularisation of repeated events through the use of the self-generated cues mnemonic, the timeline technique, and follow-up questions. Over separate sessions, 150 adult participants watched four scripted films depicting a series of meetings in which a terrorist group planned attacks and planted explosive devices. For half of our sample, the third witnessed event included two deviations (one new detail and one changed detail). A week later, participants provided their account using the MMIF, the timeline technique with self-generated cues, or a free recall format followed by open-ended questions. As expected, more information was reported overall in the MMIF condition compared to the other format conditions, for two types of details, correct details, and correct gist details. The reporting of internal intrusions was comparable across format conditions. Contrary to hypotheses, the presence of deviations did not benefit recall or source monitoring. Our findings have implications for information elicitation in applied settings and for future research on adults' retrieval of repeated events.